Increased incidence of venous thromboembolism following hip or knee arthroplasty in winter. (30th April 2020) - Jones, Christopher Wynne; Parsons, Richard; Yates, Piers J
Background: Deep vein thrombosis (DVT) and pulmonary embolism (PE) cause significant morbidity and mortality following arthroplasty. A seasonal variation in the rate of PE in arthroplasty patients in the northern hemisphere has been reported. We hypothesized that there would be a similar seasonal variation in arthroplasty patients in Australia. Methods: We performed a retrospective review of all patients who received primary and/or revision arthroplasty of the hip or knee over a 15-year period (2000–2015) across Western Australia. We identified all patients who were diagnosed with DVT and/or PE according to International Statistical Classification of Diseases and Related Health Problems, 10th Revision, Australian Modification codes. The incidence of venous thromboembolic (VTE) disease was calculated as the proportion of operations that led to this complication per 3-month seasonal period. Results: A total of 12, 507 total hip arthroplasties (THAs) and 8899 total knee arthroplasties (TKAs) were recorded during the study period. There was a total of 274 DVT and/or PE among the combined total of 21, 406 hip and knee arthroplasties performed between 2000 and 2015. There was a significantly higher rate of VTE for females than males (odds ratio (OR): 1.33, 95% confidence interval (CI): 1.03–1.71, p = 0.0293), for TKA than THA (OR: 1.60, 95% CI:1.26–2.03, p < 0.0001) and in winter than other seasons (OR: 1.51, 95% CI: 1.14–2.01, p = 0.0047). Conclusion: There is a statistically significant increase in the incidence of VTE in arthroplasty patients during the winter months in Western Australia. This finding is the first of its kind for patients in the southern hemisphere and corroborates previous studies in the northern hemisphere.